Pengembangan Bahan Ajar Konservasi Tanah Berbasis Ekopedagogi Terintegrasi Smart Environmental Monitoring untuk Meningkatkan Kemampuan Analisis Ekologis Siswa - Nike Anggraini; Khoiron Nazip (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aimed to develop a soil conservation teaching material based on ecopedagogy integrated with Smart Environmental Monitoring (SEM) to foster students’ ecological analysis skills. The research employed a research and development (R&D) approach adapted from the Borg & Gall model, consisting of four stages: preliminary study, product design, expert validation, and limited effectiveness testing on university students. The teaching material utilizes field data from soil moisture and pH sensors, as well as Sentinel-2 and Landsat 8 satellite imagery, to help students observe land cover changes and soil conditions spatially. Validation results indicated that the teaching material is very feasible with an average score of 92.3%. Effectiveness testing showed an improvement in students’ ecological analysis skills with an N-Gain score of 0.67 (moderate to high category). In conclusion, integrating Smart Environmental Monitoring based on sensors and satellite imagery into ecopedagogical teaching materials is effective in developing students’ analytical and ecological thinking skills regarding sustainable soil conservation issues. Keywords: Analytical Ecology, Teaching Material, Satellite Imagery, Ecopedagogy, Soil Conservation, Smart Environmental Monitoring